Methylenetetrahydrofolate reductase (MTHFR) C677T mutation in Turkish patients with thrombosis - Balta, Günay; Gürgey, Aytemiz (The Turkish Journal of Pediatrics, 1999)
Recently, the homozygote state for the thermolabile variant of the MTHFR gene (C677T) has been identified as a determinant of elevated homocysteine levels which are known to be a risk factor for arterial and thrombotic vascular disease. To determine whether this variant increases the risk of thrombosis, we analyzed the prevalence of the C677T substitution in the MTHFR gene in 94 patients with thrombosis and in 95 unmatched controls. Although homozygosity for the mutation was found in 12 (12.8%) of the patients with thrombosis and in only six (6.3%) of the control subjects, the difference in the prevalence of the homozygous mutant genotype between patients and healthy subjects was not statistically significant.
Keywords: methylenetetrahydrofolate reductase; MTHFR; C677T mutation; thrombosis; hyperhomocysteinemia; thermolabile enzyme